2018
DOI: 10.1186/s12890-018-0698-1
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral diaphragm paralysis: a dysfunction restricted not just to one hemidiaphragm

Abstract: BackgroundMost patients with unilateral diaphragm paralysis (UDP) have unexplained dyspnea, exercise limitations, and reduction in inspiratory muscle capacity. We aimed to evaluate the generation of pressure in each hemidiaphragm separately and its contribution to overall inspiratory strength.MethodsTwenty-seven patients, 9 in right paralysis group (RP) and 18 in left paralysis group (LP), with forced vital capacity (FVC) < 80% pred, and 20 healthy controls (CG), with forced expiratory volume in 1 s (FEV1) > 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 29 publications
0
38
0
3
Order By: Relevance
“…Furthermore, the improvement of her pulmonary function was necessary to safely perform the contralateral lung resection. In symptomatic patients with unilateral diaphragm paralysis, global inspiratory strength is reduced due not only to weakness in the paralyzed hemidiaphragm but also to impairment in the pressure generated by the non-paralyzed hemidiaphragm [8]. In our case, unilateral diaphragm plication might have influenced the contralateral diaphragm movement.…”
Section: Discussionmentioning
confidence: 83%
“…Furthermore, the improvement of her pulmonary function was necessary to safely perform the contralateral lung resection. In symptomatic patients with unilateral diaphragm paralysis, global inspiratory strength is reduced due not only to weakness in the paralyzed hemidiaphragm but also to impairment in the pressure generated by the non-paralyzed hemidiaphragm [8]. In our case, unilateral diaphragm plication might have influenced the contralateral diaphragm movement.…”
Section: Discussionmentioning
confidence: 83%
“…This point has never been demonstrated to date. Only a recent study identified a reduced pressure generated by the healthy HD after phrenic nerve stimulation in patients with contralateral unilateral phrenic nerve paralysis (9).…”
Section: Discussionmentioning
confidence: 99%
“…These connections were also studied in patients with unilateral diaphragmatic dysfunction that show dyspnoea, where an impairment is seen in the pressure generated by the theoretically healthy diaphragm [31].…”
Section: Discussionmentioning
confidence: 99%